2021
DOI: 10.1002/jcph.1910
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Performance of Population Pharmacokinetic Models of Levetiracetam in Children and Evaluation of Dosing Regimen

Abstract: Levetiracetam is a broad‐spectrum antiepileptic drug that exhibits high interindividual variability in serum concentrations in children. A population pharmacokinetic approach can be used to explain this variability and optimize dosing schemes. The objectives are to identify the best predictive population pharmacokinetic model for children and to evaluate recommended doses using simulations and Bayesian forecasting. A validation cohort included children treated with levetiracetam who had a serum drug concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Several popPK studies in the pediatric population have identified age, weight, and concomitant medications as significant covariates influencing drug clearance. [58][59][60][61][62] Through PBPK modeling, Sinha et al characterized the age-related changes in the clearance of levetiracetam in the presence and absence of concomitant enzymeinducing ASM. This work revealed that the DDI impact on levetiracetam's clearance increases with age, from 20% in children 2 years of age to 30% in adolescents, which indicates an age-dependent DDI effect.…”
Section: Levetiracetammentioning
confidence: 99%
See 2 more Smart Citations
“…Several popPK studies in the pediatric population have identified age, weight, and concomitant medications as significant covariates influencing drug clearance. [58][59][60][61][62] Through PBPK modeling, Sinha et al characterized the age-related changes in the clearance of levetiracetam in the presence and absence of concomitant enzymeinducing ASM. This work revealed that the DDI impact on levetiracetam's clearance increases with age, from 20% in children 2 years of age to 30% in adolescents, which indicates an age-dependent DDI effect.…”
Section: Levetiracetammentioning
confidence: 99%
“…Children may experience developmental changes in renal function, influencing levetiracetam clearance. Several popPK studies in the pediatric population have identified age, weight, and concomitant medications as significant covariates influencing drug clearance 58–62 . Through PBPK modeling, Sinha et al.…”
Section: Select Commonly Used Asm In Childrenmentioning
confidence: 99%
See 1 more Smart Citation